Nowy element układanki. Wczesnośredniowieczne grodzisko w Bornitach koło Pieniężna. - Wadyl, Sławomir; Martyka, Kacper (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2019)
In 2016, new remains of a stronghold in Northeastern Poland (Bornity, district Braniewo) was discovered. In a small area near Kierpajny Wielkie village, a quarter of an early Abbāsid dirham, a bronze spur, and a piece of ring of the Perm/Glazow/Duesminde type were found. Subsequent survey and excavations brought about interesting results. An analysis of the artefacts and the results of radiocarbon dating of charred wood used in the rampart construction indicate that the site was used in the late 9th and the first quarter of the 10th century. At this stage of explorations, it should be stated that the site is a significant venue on the settlement map of the 9th and early 10th centuries. Both the artefacts and the context allow to link them with the influence of the Janów Pomorski/Truso emporium.